THE STUDENTS’ PERCEPTION OF USING U-DICTIONARY IN LEARNING PRONUNCIATION AT STBA PONTIANAK - Juwita Juwita; Agus Riadi; Magpika Handayani (STBA Pontianak, 2020)
This study aims at identifying the perception of students in using U-Dictionary in learning pronunciation. Speaking is one of the most challenging abilities to develop foreign language learners such as Indonesian and one of the components of speaking is pronunciation. People often find a problem with pronunciation when they speak, read, or listen to English words. In the digital era, people can learn anything from the internet platform, such as using online learning through apps at smartphones. This study is qualitative research and the writer describe the students’ perception in using U dictionary in learning pronunciation. The writers did an observation to English study program students from the fourth semester who are eligible for this research. There were 30 students participated as respondents and all of them were interviewed in order to have true information. The result shows that most of the students think that as English study program students, learning pronunciation is important, and they perceived that the “perfect English pronunciation feature” in U-Dictionary is practical to overcome difficulties in learning pronunciation in a fun way